Wrapping technique and wrapping height interact to modify physical exposures during manual pallet wrapping. (May 2021) - Maciukiewicz, Jacquelyn M.; Whittaker, Rachel L.; Hogervorst, Kimberly B.; Dickerson, Clark R.
Abstract: Occupational tasks often involve musculoskeletal demands that contribute to injury risk. In pallet wrapping tasks, 36% of workplace claims involve over exertion and repetitive exposures (Workplace Safety and Prevention Services, 2012). Tools that modify how the wrap is handled by workers have been introduced to help mitigate over exertion and extreme postures wherever possible. A novel device has been introduced that places the required tension on the roll to mitigate these factors. However, the effect of reducing the necessary tension on the roll during pallet wrapping in limiting muscular demand and extreme postures is unknown. Fourteen healthy university aged participants completed 12 wrapping trials on a simulated pallet (2 repetitions of 2 wrapping techniques (device, hand wrapping) at 3 wrapping heights (low, medium, high)). Surface electromyography (sEMG) was measured on 6 shoulder and 2 low back muscles; anterior and middle deltoids, biceps brachii, infraspinatus, supraspinatus, upper trapezius, and erector spinae (T8 & L3). Kinematic data were collected for the torso and upper extremity and global to torso, and torso to upper arm angles were computed. Repeated measures ANOVAs were performed for the following experimental factors: 1) technique used (device or hand wrapping) and 2) the wrapping height (low, medium, high) for each muscle (8), angle (5), rating of perceived discomfort (1) and rating of perceived exertion (1). Pallet wrapping without a device required greater trunk flexion at lower heights and thoracohumeral elevation at higher wrapping heights as compared to using the device. Muscular activation increased when using the device, specifically at the higher and lower heights. Posture and muscular demands during pallet wrapping tasks are sensitive to both wrapping technique and wrapping height. Ergonomics interventions such as this device may mitigate postural risks associated with manual material handling tasks. Highlights: Using a novel pallet wrapping device reduces low back flexion while wrapping the bottom of a standard loaded pallet. The novel device reduces thoracohumeral elevation while wrapping the highest points of a pallet. A modest increase in muscular demand can be seen while using the novel device, specifically in shoulder musculature. Multiple demands involved in tasks should be investigated with relation to novel interventions. One intervention may not be suitable for all individuals, differing techniques or combined approaches may be warranted.